2021
DOI: 10.1038/s41388-021-01913-3
|View full text |Cite
|
Sign up to set email alerts
|

ZEB2 facilitates peritoneal metastasis by regulating the invasiveness and tumorigenesis of cancer stem-like cells in high-grade serous ovarian cancers

Abstract: Peritoneal metastasis is a common issue in the progression of high-grade serous ovarian cancers (HGSOCs), yet the underlying mechanism remains unconfirmed. We demonstrated that ZEB2, the transcription factor of epithelial–mesenchymal transition (EMT), was upregulated in ascites cells from HGSOC patients and in CD133+ cancer stem-like cells (CSLCs) from epithelial ovarian cancer (EOC) cell lines. SiRNA-mediated knockdown of ZEB2 in EOC cells decreased the percentage of CSLCs and reduced the colony forming poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Moreover, it correlates with worse PFS, OS, and PPS in grades II + III and III. This result is in agreement with previous studies in OV patients, suggesting its metastatic potential [18,19]. Although its expression was decreased in OV compared to normal tissue, higher EZH2 expression induced peritoneal metastasis, such as cancer stem cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, it correlates with worse PFS, OS, and PPS in grades II + III and III. This result is in agreement with previous studies in OV patients, suggesting its metastatic potential [18,19]. Although its expression was decreased in OV compared to normal tissue, higher EZH2 expression induced peritoneal metastasis, such as cancer stem cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, ZEB2 is relatively highly expressed in tumors such as leukemia, brain glioma, pancreatic adenocarcinoma, and melanoma. Previous studies suggest that ZEB2 is associated with a bad prognosis in numerous kinds of cancer [18,19,31]. Nevertheless, the prognostic significance of ZEB2 in OV remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several EMT markers have been found to be responsible for chordoma invasion and proliferation 57 . In addition, accumulating evidence shows that ZEB2 plays a pivotal role in EMT-induced malignant mechanisms, including tumor invasion, tumor recurrence 58 , drug resistance 59 , cancer stem-cell-like traits 60 , and metastasis 61 , raising the possibility that ZEB2 -associated p-EMT is involved in SBC invasiveness. According to our scRNA-seq data, the ZEB2 expression did not significantly correlate with the p-EMT program in the level of individual tumor cell.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found that miR-383-5p worked as tumor suppressor gene to suppress proliferation of ovarian cancer cells and inhibit progression of gastric cancer [ 39 41 ]. While ZEB2 worked as oncogenic genes in ovarian cancer to drive EMT transition, tumorigenesis and peritoneal metastasis [ 42 , 43 ]. The study found that ZEB2 expression in ascites of patients with high-grade serous ovarian cancer was higher than that of primary ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%